Mobile Applications with Augmented Reality and Their Impact on Teaching Students with Disabilities: A Systematic Review - Roy PARRA-TORRES; Moisés SACA-BARRAZA; Javier GAMBOA-CRUZADO; Augusto HIDALGO-SÁNCHEZ; Ronald PÉREZ-SALCEDO; Cecilia GARCIA-RIVAS PLATA; Celia YAURIS-SILVERA; Jorge ELIAS-SILUPU (Communications of International Proceedings, 2021)
Information and communication technologies (ICT) have had a significant impact on the society, affecting almost every aspect of our lives. In the field of education, ICT has transformed teaching and learning experiences, as well as aided in one of the most difficult challenges in the classroom, inclusive education. In this field, various technologies, such as video modeling (VM), serious games (SG) and gamification have been applied. However, emerging immersive technologies, such as augmented reality (AR) are among the most effective. A systematic literature review (SLR) of AR research in teaching and learning with students with disabilities was conducted. The search strategy yielded 116,420 studies, of which 104 were selected as primary studies. The studies selected for the SLR aided in answering eight research questions proposed for this study. The SLR results have found a stark trend in AR research and applications in specific disabilities, the areas of knowledge where AR is used, and the areas that use AR.
Keywords: Systematic Review; Augmented Reality; Mobile Applications; Students with Disabilities; Teaching-Learning